PEMANFAATAN SOFTWARE PRO TOOLS SEBAGAI MEDIA PEMBELAJARAN RECORDING DI SEKOLAH MUSIK PURNOMO SEMARANG (Jurnal Seni Musik, 2017)
ABSTRACT Researchers make the formulation of problems that can be studied in this research is "(1) How to use software pro tools as recording learning media at purnomo music school, (2) apasajakah supporting factor and drawing of recording learning in purnomo music school. The purpose of this research is to know, medikanripsikan and analyze (1) utilization of software pro tools as recording learning media at purnomo music school, (2) supporting and inhibiting factor of learning recording at purnomo music school. This research uses qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis is performed using data reduction, data presentation and drawing conclusions or verification. The result of the research is learning recording at Purnomo Music School for 3 months with the intensity of meeting once a week and using lecture, demonstration and question and answer method. Utilization Software Pro Tools as learning media is done with three stages namely (1) planning, Purnomo Music School has a careful planning before implementing learning recording first to prepare curriculum and learning modules; (2) implementation, recording learning in Purnomo School of Music performed in two stages. First with the preparation of music equipment and computers or laptops that are done during the learning and the second stage is the teacher or teacher to do the introduction of the tool then demonstrate how to record, mix and make music composition; (3) evaluation, evaluation is done by the teacher at the end of the learning process that is after the participants of the course follow the training for 3 months. Supporting factors in learning recording are (1) the demands in terms of music technology in the digital era; (2) the existence of youtube media as media of music development; And (3) the background of the supportive course participants. The inhibiting factors in learning recording are (1) the difference of the participants' intelligence; (2) lack of interest in theoretical learning; (3) lack of motivation of course participants in learning; (4) a less supportive environment; (5) lack of consistency of learners in meeting the schedule of the course; (6) changing the mood of course participants in learning peroses; And (7) a power outage. Suggestions that can be submitted are (1) to the manager / owner of Music School Purnomo need to evaluate the implementation of recording class course so that it can apply promotion strategy to attract more candidate course participants; (2) to instructors / instructors need to learn and apply learning methods that can improve the motivation and mood of the course participants; (3) to the participants of the course is expected to improve motivation and mood in learning recording. Keywords: utilization, software pro tools, learning media, recording